Golden Ratio and the Meaning of the Wayang Kulit Gunungan Philosophy - Ian Perasutiyo; Arif Muchyidin; Indah Nursuprianah (Journal of Mathematics Instruction, Social Research and Opinion, 2022)
Mathematics is a field of science taught since elementary school that discusses patterns or regularities of mathematical concepts and mathematical structures. One of the privileges of mathematics is that mathematics is associated with culture, and one of the responsibilities of the citizens of Indonesia is to preserve its culture. The relationship between mathematics and civilization is known as ethnomathematics. In this case, the researcher takes the culture related to Cirebon wayang kulit. The problem researchers face is that there are no rules for making shadow puppet patterns except by plagiarizing. The wayang kulit taken in this study is the wayang kulit Gunungan Cirebon. However, the researchers took the concept of the Golden ratio as a material to overcome problems in creating patterns for wayang kulit Gunungan Cirebon. This research aims to: 1). Knowing the relationship of the golden ratio in making puppet patterns in Gunungan Cirebon. 2). Knowing the relationship between the golden ratio and the wayang kulit philosophy of Gunungan Cirebon. The research method is descriptive qualitative research with interviews, observation, documentation, and measurement data collection techniques. It also uses data analysis, data reduction, presentation, and concluding. The results of this study found that there was a relationship between the golden ratio and the making of wayang kulit patterns in Gunungan Cirebon. The application of the golden ratio in the making of shadow puppet patterns also contains philosophical meanings and symmetry in it.